Respuesta :
Answer:
1489.2
Step-by-step explanation:
9*102-5.6*102=
102(9+5.6) =
102(9.0+5.6) =
102(14.6) =
102*14.6=
14.6*(100+2) =
(14.6*100+14.6*2) =
(1460+(14+.6) *2) =
1460+(28+1.2) =
1460+(28.0+1.2) =
1460+29.2=
1460.0+
29.2
=1489.2
Answer:
[tex]9\times 10^2-5.6\times 10^2=3.4\times 10^2[/tex]
Step-by-step explanation:
Given : Operation [tex]9\times 10^2-5.6\times 10^2[/tex]
To find : Perform the operation ?
Solution :
Operation [tex]9\times 10^2-5.6\times 10^2[/tex]
Taking [tex]10^2[/tex] common,
[tex]=9\times 10^2-5.6\times 10^2[/tex]
[tex]=10^2\times (9-5.6)[/tex]
[tex]=10^2\times (3.4)[/tex]
[tex]=3.4\times 10^2[/tex]
Therefore, [tex]9\times 10^2-5.6\times 10^2=3.4\times 10^2[/tex]